The Teaching of Journalistic Stylistics in the Light of Media Sociology - Spasić, Jelena Lj. (Sociološki pregled, 2019)
We consider the teaching of journalistic stylistics as a part of education for using the media and satisfying individual cultural needs. Media literacy requires diverse interdisciplinary knowledge, which also includes the ability to perceive expressive devices, that is, the style of a particular newspaper genre. In this paper we give a detailed and critical presentation of journalistic stylistics in elementary and secondary education and point to the possibilities of applying new theoretical knowledge in the field of linguistic stylistics and functional stylistics.
Keywords: media sociology; education; media literacy; journalistic stylistics; journalistic genres